An analysis of delay factors affecting labour productivity in construction using / Noor Azizah Mohd Othman - Mohd Othman, Noor Azizah (1992)
The construction industry has historically lacked significant increase in productivity . Several reasons are often cited for this limited increase in industry productivity. One of the reasons cited is the construction industry inability to model construction productivity . This thesis focuses on the development of a productivity model that provides the average construction firm with a means of measuring, predicting, and improving a given method's productivity. Although the model may not always result in the development of optimal construction method productivity, it does provides the potential for local optimization for a given construction method. The model provides the potential for increases in method productivity. The model developed referred to as the Method Productivity Delay Model (MPDM), It providees the average construction firm with a means of measuring and predicting construction method productivity. The model fucuses on method productivity parameters that are measurable and controllable by the average construction firm. Method productivity parameters are addressed by documenting productivity delays.